2005
DOI: 10.1142/s0129055x05002364
|View full text |Cite
|
Sign up to set email alerts
|

Distillability and Positivity of Partial Transposes in General Quantum Field Systems

Abstract: Criteria for distillability, and the property of having a positive partial transpose, are introduced for states of general bipartite quantum systems. The framework is sufficiently general to include systems with an infinite number of degrees of freedom, including quantum fields. We show that a large number of states in relativistic quantum field theory, including the vacuum state and thermal equilibrium states, are distillable over subsystems separated by arbitrary spacelike distances. These results apply to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 71 publications
5
91
0
Order By: Relevance
“…Later work in algebraic field theory showed that the vacuum state of the field is entangled provided that the theory satisfies certain assumptions [26][27][28][29][30][31][32][33]. This has prompted an interpretation by Reznik and his collaborators [29][30][31][32][33] in which effects similar to those of interest here (but for a scalar field) were assumed to be due to a transfer of pre-existing entanglement from the quantum vacuum to the atoms, with no requirement for any transfer of information outside of the light cone.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later work in algebraic field theory showed that the vacuum state of the field is entangled provided that the theory satisfies certain assumptions [26][27][28][29][30][31][32][33]. This has prompted an interpretation by Reznik and his collaborators [29][30][31][32][33] in which effects similar to those of interest here (but for a scalar field) were assumed to be due to a transfer of pre-existing entanglement from the quantum vacuum to the atoms, with no requirement for any transfer of information outside of the light cone.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…An alternative interpretation has been suggested based on algebraic quantum field theory, where the quantum vacuum is considered to be an entangled state [21][22][23][24][25][26][27][28][29][30][31][32][33]. In that case, the effects of interest here could be interpreted instead as being due to the transfer of entanglement from the quantum vacuum to the atoms without the need for an exchange of particles or information outside of the forward light cone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact is borne out operationally by the ability to swap this entanglement to local quantum systems ('detectors') through local interactions [4]. Local hidden-variable models cannot account for the long-distance correlations due to this entanglement [4,5], which decrease at a rate slower than − L cT exp [ ( ) ] 3 , where L is the separation and T the duration of the detector-field coupling. Other types of vacuum correlations, such as true multi-region entanglement [6] and full nonlocality [7,8], are also possible.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a local hidden-variable model cannot account for these correlations [1,2], and that as a function of the separation between the regions, L, and the duration of the coupling, T , the entanglement decreases at a slower rate than e −(L/cT ) 3 . It is, therefore, natural to ask whether the vacuum admits other types of these kinds of correlations, i.e.…”
mentioning
confidence: 99%